Trust in trade: A global perspective on health certification - Grace, Delia (World Organisation for Animal Health, 2020)
Trade in livestock and livestock products can bring about great benefits, but also substantial risk to animal and human health with high economic, social and environmental impacts. Livestock products are also especially vulnerable to food fraud. In order to mitigate risk and prevent fraud, most animal trade requires health certification by a competent authority, backed by systems and processes that create trust and confidence in importers. Among Veterinary Services which have undergone a structured assessment of performance, most find the need to improve their authority and/or capability for health certificates and for transparent disease reporting. Health certification is trusted when it is legal, carried out by an adequately performing authority, implemented by competent persons, supported by technical evidence, and validated by third parties and when the process is transparent, predictable and free from conflict of interest. The large and growing trade in animals and their products is a testimony to the effectiveness of the current process and the trust of importers. Nonetheless, there is considerable scope for further improvement especially by improving the legal framework, building capacity of Veterinary Services, increasing trust in signing authorities, validating the certification process, and making the process of certification more efficient and predictable.